Can the snowline be used as an indicator of the equilibrium line and mass balance for glaciers in the outer tropics? - Rabatel, Antoine (2012)
Original abstract: Because the glacier snowline is easy to identify on optical satellite images and because in certain conditions it can be used as an indicator of the equilibrium line, it may be a relevant parameter for the study of the relationships between climate and glaciers. Although several studies have shown that the snowline altitude (SLA) at the end of the hydrological year is a good indicator of the equilibrium-line altitude (ELA) for mid-latitude glaciers, such a relationship remains conjectural for tropical glaciers. Indeed, unlike in mid-latitudes, tropical climate conditions result in a distinct seasonality of accumulation/ablation processes. We examine this relationship using direct field ELA and mass-balance measurements made on Glaciar Zongo, Bolivia (~16° S), vand Glaciar Artesonraju, Peru (~9° S), and the SLA retrieved from satellite images acquired in the past two decades. We show that on glaciers in the outer tropics: (1) ablation is reduced during the dry season in austral winter (May-August), the SLA does not change much, and satellite images acquired between May and August could be used to compute the SLA; and (2) the highest SLA detected on a number of satellite images acquired during the dry season provides a good estimate of the annual ELA. However, as snowfall events can occur during the dry season, the SLA detected on satellite images tends to underestimate the ELA. Thus, we recommend validating the SLA computed from satellite images with field data collected on a benchmark glacier before measuring the SLA on other glaciers in the same mountain range for which no field data are available. This study is a major step towards extending the measurement of glacier parameters (ELA and mass balance) at the scale of a whole mountain range in the outer tropics to better document the relationships between climate and glaciers.